Modal Analysis of a Trapezoidal Violin Built after the Description of Félix Savart - Tim DUERINCK; Ewa SKRODZKA; Bogumił B.J. LINDE (Archives of Acoustics)
One-dimensional experimental modal analysis of an unvarnished trapezoidal violin built after the descriptions of F. Savart and an anonymous trapezoidal violin on display in the Music Instrument Museum of Brussels is described. The analysis has revealed ten prominent modes. A mode that may potentially play a role of the “tonal barometer” of the instrument is pointed out. The mode shapes are symmetric and of high amplitude, due to the construction of the instrument. Subjective evaluation of the sound quality demonstrated no pronounced difference between the trapezoidal violin and a normal violin.